Crafting a tooling idea into a new domestic landscape re.visited - Costa, Carlos Casimiro da (2011)
Crafting a tooling idea into a new domestic landscape re.visited: This document pretends to establish sensible paths that converge for a more sustainable world. In this sense the emphases is in verifying and characterize the user’s ways of life and there real needs in finding sustainable regenerative definitions. The requirement to interpret different contexts of new social and peripheral life-styles, developing adaptative crafty tools that promote forms, services, products and systems that do not compromise well being but to establish a symbiotic relation between ambient and the new and necessary technologies. Design criteria will allow an interpenetreural emphasis in this domestic living landscape, and their relations for a flexible and fluid system. The idea of one unlimited progress and unlimited growing process of product systems (classical and cycle point of view: production, consumer and economic development) has been an issue for arguing the simplicity models that today have a no more recognizable path for sustainability (Perejaume, 2000). The technological innovation and design need a new kind of dialogue between science and society as the origin of the creative process of mankind and there interdisciplinary, systemic and plural ways of thinking (Bonsiepe, 1985) .The project is a process, an attitude before being a trade (Mari, 1997) the sustainable ways of thinking needs to understand the responsibility of the designer and the role that he represents in the management system of a product industry (Papanek, 1971). The awareness of thinking in new products as open source design practice for a radical proceeding inside ecological times (Manzini, 2001). The ‘new’ scenarios, define mobility, as a main factor in household strategy by researches in series of self-packaging and do-it yourselfer modular systems that promote an itinerant portable well-being. This perspective demands a scenario where there is the possibility of including in-services into this modular products and self-assembly condition items for operative/functional regenerative potential tooling. This process has is origin into one empiric mobile research representing two parts of the same problems: adaptable living household into one semi-sphere of an incessant mobility and a research for the knowledge into one unsustainable dwelling. This issue includes the study of itinerant life-styles, especially students, teachers or other mobile users promoting sensibilities for craft or the ability for incorporate reacting tools for acting into self recognition and memory identification. The necessary interpretation of different and plural habitats put together ‘new’ forms of living objects but also their simple ephemeral edifications in their frequent migrations. This represents a total alienation with this life-cycle-products criteria’s and quality in a sustainable society, also represents a full system that needs eco-instruments to transform a low material and energy intensity. These special users are active part of the solution and their convenience in the development of the promising scenarios and their relations.